Impact of regioregularity on the solubility parameters of poly(3‐hexylthiophene). Issue 19 (18th June 2022) - King, McKenna; Gottlieb, Danielle; Boucher, David
Abstract: The solubilities of four P3HT samples of varying regioregularity (rr = 58%, 86%, 93%, and 96%) are measured in 18 organic solvents, and the solubility data are used to calculate the partial solubility parameters (SPs) ( δ D, δ P, δ H ) of the samples using the functional solubility parameter (FSP) approach. The FSP results show that the δ P and δ H parameters increase with increasing regioregularity. The results reveal that the anomalously large δ P and δ H SPs regioregular P3HT previously reported in the literature are attributable to the microstructure (regioregularity) of the P3HT polymer, and that as that as the regioregularity of P3HT increases the polymer can engage in stronger associative interactions with the solvent. Complementary computational analyses of hexamer model systems using Gaussian16 and AIMll software, reveal variations in electronic characteristics and topological parameters consistent with the regioregular‐dependent increases in δ P and δ H. This research may aid in modifying the fundamental and/or practical framework of SP theory to account for the effects of polymer microstructure and polymorphism. Abstract :